Hashtag Activism: Exploring The Church Must Vote Campaign in Nigeria - Confidence Amadi, Temple Uwalaka, Bigman Nwala & (Covenant Journal of Communication, 2020)
Socio-political activism and its relationship with digital media diffusion is an on-going subject of considerable debate among observers and scholars globally. This work creates a research trajectory on Nigeria by investigating the contributions of social media in the implementation of The Church Must Vote campaign. It examines the effects of connective action and clicktivism on political mobilization and evaluates how Christians used social media to increase their civic vitality during the 2019 general elections. A total of 6,951 online content, including 42 YouTube videos posted by the users of the hashtag, #thechurchmustvote, were explored via social networking analysis. Findings show that social media played a significant role in the success of the campaign and served as education channels to advise Christians on the need to participate in the elections. The impressive outcome elicits the recommendation that Nigerians should consider hashtag activism or clicktivism as a valuable political engagement system.